Utility of negative pressure wound therapy with instillation in a burn center. Issue 4 (October 2018) - Blome-Eberwein, Sigrid; Lozano, Daniel; Amani, Hamed
Highlights: Burn, contaminated wound, and necrotizing fasciitis requires multi-modal treatment. NPWTi-d may offer clinical benefit during management of these complex wounds. NPWTi-d use in 21 patients is described. NPWTi-d use led to wound cleansing, expedited coverage, and decreased patient pain. All wounds were closed without added complications after NPWTi-d treatment. Abstract: Introduction: Current standard of care for complicated and deep burn wounds includes removal of devitalized tissue, infection treatment/prevention, temporary coverage, and pain management before and during wound closure. Negative pressure wound therapy with instillation and dwell time (NPWTi-d) utilizes both negative pressure and instillation of topical wound solutions for wound cleansing and removal of infectious materials. We describe our experience using NPWTi-d for complicated wound management in a burn center. Methods: Twenty-one patients were included in a retrospective analysis of burn wounds (n = 15) or wounds resulting from necrotizing fasciitis (n = 6). Patients received systemic antibiotics and underwent wound debridement as indicated. NPWTi-d was initiated by instilling Dakin's solution (quarter strength), mafenide solution, or normal saline with a dwell time of 5–10 min followed by 4–6 h of NPWT at −75, −100, or −125 mmHg. Results: Mean percent total body surface area (TBSA) was 11.6% for the burn wounds and 10.0% for the necrotizing fasciitis wounds. Mean duration of NPWTi-d therapy was 10.0 days prior to wound closure by split-thickness skin graft (n = 13), graft and flap (n = 3), primary intention and graft (n = 1), secondary intention (n = 1), or amputation (n = 3). All wounds were successfully closed and no complications occurred during NPWTi-d treatment. Conclusions: In these patients, NPWTi-d provided safe and effective adjunctive therapy for complicated wounds resulting from burns or necrotizing fasciitis.